Synthesis and Characterization of 5- Amino-1, 3, 4-Thiadiazole-2-thiol and its Amine Group Derivatives - Mustafa M. Shihab (Journal of Global Pharma Technology, 2016)
This work includes preparation of 5-Amino-1,3,4-thiadiazole-2-thiol from thiosemicarbazide with Carbon disulfide (CS2) and KOH as catalyst. Also reaction of 5-Amino-1,3,4-thiadiazole-2-thiol with different aromatic aldehydes by using glacial acetic acid as catalyst to synthesis of some new Schiff bases derivatives that coupled with thioglycolic acid to synthesis five- member ring heterocyclic compounds derivatives. All synthetic compounds were definited by their melting point, FT-IR spectra and 1H-NMR spectra for some of them.Keywords: 5- Amino-1, 3, 4-thiadiazole-2-thiol, Thiosemicarbazide, Schiff bases, heterocyclic compounds, thiadiazole.